A technical analysis of Sam Kendricks - Bussabarger, D. (Track Coach, 2015)
American vault star Sam Kendricks is best known for his modest hand grip of 15`5" and his record setting push-off of 4` 5¾" on his PR 5.86/19`2¾" vault. Note that this is the highest verified push-off relative to the height of the bar (extra height above the bar of course does not count for record purposes). Kendricks`s outstanding push-off is of special interest to the writer. Referring back to Brian Sternberg`s WR 16`8" vault in 1963, it has long seemed to the writer that fiberglass vaulters have yet to fully exploit potential push-off distance (for more details see Track Coach 169 and 192). Keep in mind that all first generation vaulters, including Sternberg, were just learning to bend the pole and therefore used poles rated roughly equal weight in stiffness. Prior to Kendricks, the best verified push-off known to the writer was 4`2½" by Joe Dial on his AR 19` 6 !/2" in 1987. So Kendricks`s new record represents a major improvement in performance. Kendricks uses a 15` 9"/207 lb USTEssx carbon fiber pole. At 6`1"/170 he is about average size for an elite male vaulter. However 9.31 velocity over the last 5m of his run and a 22`1" long jump best put him in the lower end of the spectrum for speed and springing power.